PENGARUH MOTIVASI DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA: (Studi Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Majalengka) - DUDUNG ABDULLAH; FISKA RAHMAH SEPTIANY (IKOPIN, 2019)
Unemployment is one of the economic problems that often occur in developing countries. One effort that can be done to reduce spending by encouraging the creation of new entrepreneurs. As young people who are the nation's successors, students can become actors of entrepreneurship. Students can start entrepreneurship by motivating themselves and learning knowledge about entrepreneurship because in entrepreneurship knowledge implanted attitudes and knowledge about strong entrepreneurs. This study aims to study the motivation and knowledge of companies that are oriented to the students of the Faculty of Economics and Business, Majalengka University. The population in this study was all students of the Faculty of Economics and Business, with a total sample of 100 people. The method used is a survey method using descriptive verification. The analysis tool uses multiple regression analysis, coefficient of determination, and hypothesis testing for partial using the t test while for simultaneous using the F test. The results of research on motivation and knowledge about category are very high, and interest in entrepreneurship is high. Hypothesis test results partially indicate whether simultaneous motivation and knowledge are significant for entrepreneurial interest. Because the motivation and knowledge of the factors driving the increased interest in entrepreneurship, the higher of the motivation and knowledge possessed by students will increase the interest in entrepreneurship.